Neurologic manifestations of Zika virus infection - Zunt, Joseph R. (2017)
Zika virus is a flavivirus transmitted via mosquito bite, blood transfusion, sexual intercourse or from mother-to-child during gestation. Although neurologic complications of Zika virus infection are rare, Guillain-Barré syndrome (GBS) is the most common manifestation and typically develops soon after the initial systemic manifestations of Zika virus infection. This syndrome typically starts in the distal limbs with symmetric sensory abnormalities and progresses to involve weakness and decreased or absent deep tendon reflexes. Severe cases may also involve respiratory and cardiovascular impairment requiring care in an intensive care unit, and ventilator or circulatory support. A review of 166 published cases of GBS associated with Zika virus is notable for lower mortality than seen with sporadic GBS, but limited data regarding long-term outcome. When available, treatment with intravenous IgG (IVIg) or plasmapheresis, can reduce the severity and duration of symptoms.